EFFECTIVENESS OF THE FLOOD EDUCATION MODEL IN GORONTALO CITY - FADLY ACHMAD; HUSAIN SYAM; AHMAD RIFQI ASRIB (Pascasarjana Universitas Negeri Makassar, 2024)
In mitigating the flood disasters that often hit Gorontalo City, the participation of all parties is needed, starting from the local government, campus and community. Disaster education at the community level must be used as an initial lesson in disaster mitigation. One effort that can be made is by mapping land types in Gorontalo City which is then disseminated to technical agencies (PUPR) in order to reduce the risk of flooding in vulnerable areas. The research began with technical mapping of soil types in flood areas in Gorontalo City. Maps were analyzed using GIS applications. The resulting GIS map was then submitted to the Gorontalo City PUPR Service. The research results show that the dominant clay soil is spread across 6 sub-districts in Gorontalo City, namely Kota Selatan, Kota Tengah, Kota Utara, Kota Timur, Dungingi and Sipatana Districts. Some of them are in Kota Barat and Dumbo Raya sub-districts. Meanwhile, in Hulonthalangi District, sandy soil is more dominated; the educational model regarding technical maps of soil types received a positive response from the Gorontalo City PUPR Service.